Gibberellins regulate masculinization through the SpGAI‐SpSTM module in dioecious spinach - Zhang, Yu‐Lan; Wang, Li‐Ying; Yang, Yi; Zhao, Xu; Zhu, Hong‐Wei; You, Chen; Chen, Ning; Wei, Shuai‐Jie; Li, Shu‐Fen; Gao, Wu‐Jun (The Plant journal : for cell and molecular biology, 2024)
SUMMARY The sex of dioecious plants is mainly determined by genetic factors, but it can also be converted by environmental cues such as exogenous phytohormones. Gibberellic acids (GAs) are well‐known inducers of flowering and sexual development, yet the pathway of gibberellin‐induced sex conversion in dioecious spinach (Spinacia oleracea L.) remains elusive. Based on sex detection before and after GA3 application using T11A and SSR19 molecular markers, we confirmed and elevated the masculinization effect of GA on a single female plant through exogenous applications of GA3, showing complete conversion and functional stamens. Silencing of GIBBERELLIC ACID INSENSITIVE (SpGAI), a single DELLA family protein that is a central GA signaling repressor, results in similar masculinization. We also show that SpGAI can physically interact with the spinach KNOX transcription factor SHOOT MERISTEMLESS (SpSTM), which is a homolog of the flower meristem identity regulator STM in Arabidopsis. The silencing of SpSTM also masculinized female flowers in spinach. Furthermore, SpSTM could directly bind the intron of SpPI to repress SpPI expression in developing female flowers. Overall, our results suggest that GA induces a female masculinization process through the SpGAI‐SpSTM‐SpPI regulatory module in spinach. These insights may help to clarify the molecular mechanism underlying the sex conversion system in dioecious plants while also elucidating the physiological basis for the generation of unisexual flowers so as to establish dioecy in plants. Significance Statement Using environmental factors such as hormones to induce sex conversion is an important approach to studying dioecy sex differentiation, which is a special character closely related to flowering, reproduction, and fruiting. In our research, exogenous GA3 can induce functional masculinization of individual spinach, and the GA‐regulating pathway was established: GA‐SpGAI‐SpSTM‐SpPI. This study provides new ideas and theoretical support for studying the sex differentiation mechanisms of spinach and other dioecious plants.